2022
DOI: 10.2147/jhc.s358082
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Therapy for Hepatocellular Carcinoma: Current Updates and Outlook

Abstract: Hepatocellular carcinoma (HCC) has emerged the culprit of cancer-related mortality worldwide with its dismal prognosis climbing. In recent years, ground-breaking progress has been made in systemic therapy for HCC. Targeted therapy based on specific signaling molecules, including sorafenib, lenvatinib, regorafenib, cabozantinib, and ramucirumab, has been widely used for advanced HCC (aHCC). Immunotherapies such as pembrolizumab and nivolumab greatly improve the survival of aHCC patients. More recently, synergis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 302 publications
(360 reference statements)
0
26
0
Order By: Relevance
“…Subgroup analyses showed that treatment with Sorafenib led to a better survival benefit in HCV patients compared to HBV ones [ 52 , 53 ]. Moreover, TTP was also significantly longer for HCV patients than for HBV ones (6.5 vs. 4.0 months, respectively, p = 0.05) [ 54 ]. In support of these data, a meta-analysis of Phase III trial results confirmed a survival benefit for patients with HCV etiology, compared to HBV [ 55 ].…”
Section: Targeted Therapiesmentioning
confidence: 99%
“…Subgroup analyses showed that treatment with Sorafenib led to a better survival benefit in HCV patients compared to HBV ones [ 52 , 53 ]. Moreover, TTP was also significantly longer for HCV patients than for HBV ones (6.5 vs. 4.0 months, respectively, p = 0.05) [ 54 ]. In support of these data, a meta-analysis of Phase III trial results confirmed a survival benefit for patients with HCV etiology, compared to HBV [ 55 ].…”
Section: Targeted Therapiesmentioning
confidence: 99%
“…A recent report suggested that neutrophils hamper the efficacy of ICIs, especially in non-alcoholic steatohepatitis (NASH)-induced HCC ( 69 ). The neutrophils to lymphocytes ratio (NLR) may serve as indicators of systemic inflammation, and the ratio is increased in individuals with HCC, owing to relative increases and decreases in neutrophils and lymphocytes, respectively ( 70 ). The association between an elevated NLR and adverse clinical outcomes in individuals with HCC has been demonstrated consistently for several treatment options for HCC, e.g.…”
Section: Blood-based Biomarkers For Immune-based Treatment In Advance...mentioning
confidence: 99%
“…Over several decades, novel drugs have developed to regulate specific steps of the mechanisms in hepatocarcinogenesis and its progression. Systemic therapeutic options that have been developed for advanced hepatocellular carcinoma include molecular-targeted agents (multi-tyrosine kinase inhibitor (TKI)), cytotoxic chemotherapy, immunotherapy, and combination therapy [100].…”
Section: Treatments For Liver Cancermentioning
confidence: 99%